2020
DOI: 10.1002/met.1931
|View full text |Cite
|
Sign up to set email alerts
|

Linking weather patterns to regional extreme precipitation for highlighting potential flood events in medium‐ to long‐range forecasts

Abstract: Medium‐ to long‐range precipitation forecasts are a crucial component in mitigating the impacts of fluvial flood events. Although precipitation is difficult to predict at these lead times, the forecast skill of atmospheric circulation tends to be greater. The study explores using weather patterns (WPs) as a preliminary step in producing forecasts of upper‐tail precipitation threshold exceedance probabilities for the UK. The WPs are predefined, discrete states representing daily mean sea‐level pressure (MSLP) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 41 publications
(48 reference statements)
1
32
0
Order By: Relevance
“…Büeler et al (2021), for example, analysed the skill of the ECMWF forecasts in predicting seven weather regimes over Europe and the horizon of skilful predictions was about 14 days. Richardson et al (2020b) showed that the ECMWF 51-member model has a predictability limit of about 15 days for the eight UK-defined regimes, when analysing the performance based on BS and considering a 1-day flexibility window in the occurrence of the patterns. Increased model skill is also observed in this study when considering a flexibility window in the occurrence of the patterns (not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Büeler et al (2021), for example, analysed the skill of the ECMWF forecasts in predicting seven weather regimes over Europe and the horizon of skilful predictions was about 14 days. Richardson et al (2020b) showed that the ECMWF 51-member model has a predictability limit of about 15 days for the eight UK-defined regimes, when analysing the performance based on BS and considering a 1-day flexibility window in the occurrence of the patterns. Increased model skill is also observed in this study when considering a flexibility window in the occurrence of the patterns (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…These patterns can be used as a prognostic tool for extremes and provide skilful predictions of surface weather variability at longer lead times. In a recent study, it was shown that UK‐specific large‐scale patterns can support the predictability of extreme rainfall at medium‐range forecasts (Richardson et al ., 2020b). The same patterns have also been used to infer information about the likelihood of coastal flooding (Neal et al ., 2018) and of droughts (Richardson et al ., 2020a) at medium‐ and extended‐range lead times.…”
Section: Introductionmentioning
confidence: 99%
“…CCs can analyse the impact of both natural climate variability and external anthropogenic forcing at the regional scale. Beyond mirroring changes in mean climate, CCs also represent a powerful tool to investigate extreme events, which are often associated with specific atmospheric circulation patterns (Richardson et al ., 2020; Mastrantonas et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the climatology centred on 1 June would include all days between 12 April and 21 July (±50 days) from all years in the 39‐year period. A 101‐day period is roughly equivalent to a 3‐month climatology, which is often used as a definition for a seasonal climatology and has been used in other related studies (Richardson, Neal, et al, 2020). Step 2 —Calculate weather pattern empirical probabilities of exceeding the 95th percentile …”
Section: Methodsmentioning
confidence: 99%